Myringoplasty in wet and dry ears: an observational study in a tertiary care center - Rao, S. Umamaheswara; Reddy, K. Samatha; Pakanati, Siva Subba Rao; Chandramouli, S. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Chronic otitis media is the most common cause of hearing impairment in the developing countries with serious effects. The aim of the study was to compare the outcome of myringoplasty in dry and wet ears in tubo-tympanic type of chronic otitis media (COM) with respect to graft uptake and hearing improvement. Methods: This is an observational study done in the department of ENT, Mamata medical college, Khammam, during the study period of September 2019 to February 2021 on 40 patients of tubo-tympanic type COM. On simple random basis selected patients underwent myringoplasty by underlay technique. All patients were evaluated during post-operative follow-up. Results: In our study, majority of patients were in the age group of 26 to 45 years with slight female preponderance, with male to female ratio (0.73:1). In our study, the successful graft uptake was seen 90% in dry ears and 85% in wet ears, which seems to be not significant in difference. With respect to hearing improvement, post-operatively there was significant improvement in both the groups, when compared to pre-operative hearing. The maximum improvement in average hearing threshold after surgery, in dry ears with large perforation (12.66dB) and in wet ears with small central perforation (12.44dB) was almost equal. Conclusions: In this study, the success rate of graft uptake and hearing improvement is found almost equal in dry and wet ears by using underlay technique of myringoplasty.